Concept of the Word accordinhg to the Christian and the Muslim Tradition - Kunev, Zdravko (Forum Theologicum Sardicense, 2025)
Zdravko Kunev, Concept of the Word according to the Christian and the Muslim Tradition. The article examines the concept of the “Word” in the three major mono-theistic religions—Judaism, Christianity, and Islam. It focuses on the differences in interpreting the Word as both sacred utterances of God and as human expressions through which God communicates. The article also considers the fundamental differences in the understanding of the Word between Christianity and Islam. In Christianity, the emphasis is on Jesus Christ as the incarnate Word, while in Islam, the focus is on Isa (Al-Masih) as a Word of Allah and the Qur'an, which Islamic tradition regards as a divine revelation sent down from heaven by Allah.